Estilo de vida y percepción social de estudiantes universitarios según género - Buitrón Aranda, Aymé Gabriela (2014)
This study has as purpose to explain thesocial reality and personal life perceptionof an area of young university studentsin Peru, emphasizing genre difference;this article will have basis on the analysisperformed this year, according to the datacollected in 2012 between students ofUniversidad Peruana Cayetano Heredia.